Information services and digital literacy in search of the boundaries of knowing - Huvila, Isto. (Oxford, UK Chandos Pub., 2012)
Despite new technologies, people do not always find information readily. This book is about the role of information services and digital literacies in the age of the social web. Do people still need help in finding the information they need, and if so, why? What can new tools and techniques make easier? Who needs help, and with what? The author provides an alternative perspective for understanding the context of information services and digital literacy and argues that a central problem in the age of the social web and the culture of participation is that we do not know the premises of how we know, and how ways of interacting with information affect our actions and their outcomes. Information seeking and finding is always a question of crossing and expanding boundaries; between our earlier experiences and the unknown. We may not yet be well enough acquainted with the landscape of digital information to understand the following: how we know; where the boundaries lie; how to cross them; and what consequences our actions have.
Keywords: Digital media; Information services; Information literacy